Seating and Driver Interactions in Automated Vehicles: Development of a User Study Investigating Seating Positions and HMIs - Makris, Melina (My University, 2020)
The technology for automated vehicles is developing rapidly, turning drivers into passengers, having end users demand a more relaxed seating position. The reclined seating position is one of the most popular expectation among end users, nevertheless, there is a lack of investigations of reclined seating positions in highly automated vehicles in dynamic environments. To ll this gap, the thesis proposes a valid user study methodology to enable assessing the end user preferences and requirements on the reclined seating position, as well as its related HMIs between active and automated driving mode, and between upright and reclined seating position. Moreover, it evaluates usability problems of the reclined seating position and its related HMIs, based on the seating and HMIs of a prototype vehicle provided by Autoliv. The research approach encompasses methods such as Failure Mode and E ect Analysis, subjective data collection methods and applied meta-methods to develop a valid user study method. Not only did the approach yield useful insights for the development of a user study method of high degree of validity, but it also helped identify ethical aspects to consider when conducting user studies with human subjects. For the evaluation of the reclined seating position and its related HMIs in Autoliv's prototype vehicle, methods such as heuristic evaluation and semi- structured interviews were utilised. This approach generated ndings of usability problems of the reclined seating position and HMIs. The project found that in order to conduct a valid user study assessing end user preferences and requirements on the reclined seating position and its related HMIs, six aspects must be considered. These aspects include; recruiting relevant participants, providing them with consistent tasks, providing adequate time constraints, avoiding social in uences, utilising appropriate data collections methods and carrying out a pilot study. Moreover the project recommended a set of brief guidelines on how to re ne the reclined seating and its HMIs in Autoliv's prototype vehicle to increase usability. These ndings set the basis for future investigation of the end user requirements and preferences of a reclined seating position and related HMIs in highly automated vehicles.